Combination antiplatelet/antithrombotic regimens after stenting: Are we forcing too much in this decision?. Issue 4 (15th March 2021) - Nicolas, Johny; Dangas, George
Key Points: Patient‐centered care entails balancing the risks and benefits of each antithrombotic therapy regimen. When assessing the risk–benefit tradeoffs of each antithrombotic therapy, all outcomes must be taken into account rather than focusing on a single outcome such as stent thrombosis. Additional randomized clinical trials are needed to establish the optimal antithrombotic therapy regimen in all patients, especially in those at high risk for bleeding and ischemic events.